CICC Group training course: October 1991- March 1992, Tokyo, Japan - Lee, A. (Perpustakaan Universiti Malaya, 1992)
The Center of the International Cooperation for Computerization Japan (CICC Foundation) offers various training programmes in computer and information technology. One such training programme is the 6-months practical training course in computer technology held in Japan. Participants from developing countries took part in an orientation programme on Japanese society and living in Japan, study tours and computer training. The training offers participants the opportunity to witness and experience at first-hand Japanese developments and progress in computer and information technology.